Payday loans in the press: a discourse-mythological analysis of British newspaper coverage of the payday loan industry. Issue 1 (1st January 2020) - Budd, Kate; Kelsey, Darren; Mueller, Frank; Whittle, Andrea
ABSTRACT: This paper analyses media coverage of payday loans in order to understand how a moral case for state intervention and regulation was constructed through forms of mythological storytelling. By analysing the archetypal qualities of media discourse, we can see how particular ideas are legitimised through the ideological mechanisms of moral stories. Stories drew on mythology of the "other world, " the flood, and the tragedy. Archetypal roles were constructed for the borrower as victim and the payday loan firm as villain or trickster, with the latter drawing on religious and literary figures as archetypes. This paper has shown how, regardless of the ideological positioning of individual newspapers, a moral plot was crafted which framed the industry as a problem that ultimately served to justify state regulation of the industry.